Recovery of the grizzly bear at the intersection of law and science - Greenwald, Noah (Frontiers in Conservation Science, 2023)
Over the last 30 years, there have been numerous legal battles over recovery of the grizzly bear. These battles have brought to fore a question central to implementation of the Act, namely is the goal of recovery to merely remediate extinction risk or to affect broader ecosystem recovery. I systematically reviewed court decisions related to the grizzly bear's recovery plan, efforts to remove protections for grizzly bears, and challenges to logging, mining and other projects with impacts to grizzly bears. A legal challenge to the grizzly bear's 1993 recovery plan forced the Service to develop habitat-based recovery criteria for the Greater Yellowstone Ecosystem. Legal efforts to reopen the recovery plan and expand recovery into additional areas of historic range, however, were unsuccessful, leaving the scope of recovery largely at the discretion of the U.S. Fish and Wildlife Service. Lawsuits brought by multiple conservation groups, tribes and individuals have constrained this discretion, twice stopping the agency from stripping Greater Yellowstone grizzly bears of federal protections. This has allowed the population to grow and forced consideration of the impact of removing protections for Greater Yellowstone bears on overall recovery as a requirement of any future effort to remove protections. Court decisions were issued on 65 challenges to projects impacting grizzly bear habitat, including 44 involving logging and related road construction, seven mining, four livestock grazing, two recreation, five oil and gas leasing and three road projects, leading to 11 of these projects being stopped and nine modified. Lawsuits were also filed to stop hunting in four instances, trapping in one, predator control in one and railroad mortality in two, as well as activities that disturb bears, including helicopters in two instances and snow mobile use in another, resulting in four being stopped and another 3 modified. Protection of the grizzly bear under the Endangered Species Act, along with subsequent litigation, has led to substantial changes in management of public lands in the four recovery zones with grizzly bear populations, but not elsewhere in the species' range. Overall, the legal system is an important, but often overlooked, part of recovery of endangered species.